Pencegahan Stunting Melalui Penguatan Ketahanan Pangan Bagi Masyarakat Desa Kumpi Kecamatan Lembo Kabupaten Morowali Utara - Delfince Tjenemundan; Feliks Arfid Guampe; Olvit Olniwati Kayupa; Cirtye Labesani; Melky Alfian (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Stunting is the most serious nutritional problem in Indonesia, caused by inadequate nutritional intake. This condition is characterized by impaired growth, where children's height is shorter compared to the average height of children their age. Stunting can be prevented if interventions are carried out before the child reaches the age of two to five years. In Kumpi Village, one child was found to be at risk of Stunting. To prevent Stunting, knowledge transfer through training and community mentoring is needed, one of which is by strengthening food security. This activity uses an active participation method and involves various activities such as